DEVELOPMENT OF INSTRUCTIONAL SCENARIOS FOR CHEMISTRY RELATED TO MILITARY MISSIONS FOR PRE-CADET AT ARMED FORCES ACADEMIES PREPARATORY SCHOOL IN UNDER COMMAND OF NATIONAL DEFENSE STUDIES INSTITUTE - Mornpan, Yanika; Srisa-ard, Sirirat; Pilanthananond, Nataya (Journal of Educational Review Faculty of Education in MCU, 2022)
The purposes of this research were 1) to develop instructional scenarios for chemistry from Armed Forces Academies Preparatory School curriculum related to military mission. 2) evaluate the quality of instructional scenarios. This research is Basic Research. The methods of this research were 1) prepare to related chemistry from Armed Forces Academies Preparatory School curriculum and military missions. 2) develop Instructional Scenarios for Chemistry Related to Military Missions. 3) evaluate the quality of instructional scenarios by 24 experts that acquired by purposive sampling from who expertise in military missions, teachers of chemistry and science studies. Statistically analyzed data including mean and standard deviation. The results were 1) 2 military missions related to chemistry were prevention caused by toxic or chemical substances, leakage of radiation from nuclear weapons, the danger of biological weapons and chemicals substances in the manufacture of equipment to support military mission. 2) development of instructional scenarios related to military missions consisted of 13 concepts. 3) most of the experts were agreed with instructional scenarios at the highest level. Learning activities, materials and evaluations were appropriate and various for stimulate students, and developing higher-order thinkings.